The United Nations After 75: Assessing Current Understandings, Charting Fruitful Research Agendas. Issue 4 (8th August 2022) - Mahmood, Zuhaib; Beardsley, Kyle; Newton, Christopher; Roy, Chhandosi; Kathman, Jacob D.; Tucker, Colin; Nomikos, William G.; Villa, Danielle N.; Binder, Martin; Allen, Susan; Yuen, Amy; Passmore, Timothy J.A.; et al.
Abstract : From its capacity for deploying joint operations in conflict zones to its status as a standard-bearing forum for international behaviour, the United Nations has asserted its relevance in a diverse array of issues and conflicts around the world. Equally as diverse has been the scholarship surrounding the United Nations over the past several decades. This collection of essays provides a snapshot of these diverse lines of scholarship, highlighting existing scholarship on a range of topics, as well as identifying areas of opportunity for future scholarly work on these topics. Taken as a whole, this forum more broadly provides insight into core pillars of the United Nations' mission–including the maintenance of peace and security; fostering friendly relations between nations; promoting human rights and humanitarian goals; and encouraging cooperation and harmonization of interests between nations. Moving forward, it is our hope that this collection will serve as a sprigboard for inspiring future work to both build and expand upon the insights from the past several decades of scholarship on the United Nations.